2013
DOI: 10.1111/jtsb.12046
|View full text |Cite
|
Sign up to set email alerts
|

Specific Organizational Citizenship Behaviours and Organizational Effectiveness: The Development of a Conceptual Heuristic Device

Abstract: Organizational citizenship behaviour has generally been associated with organizational effectiveness. However, recent research has shown that this may not always be the case and that certain types of organizational citizenship behaviour such as compulsory citizenship behaviour, may be inimical to the fulfillment of formal goals and organizational effectiveness. Using military historical and business organizational secondary data, the paper maintains that extreme variance in either organizational (task) or pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…However, the heuristic is unable to articulate formally the distribution of personal and organizational citizenship behavior that leads to ECB. It is maintained in the current paper that Theil's [8] "evenness of spread" concept can provide the basis for a sounder, more formal and detailed development of the original Coldwell and Callaghan [23] model. Theil [8] uses Shannon's notion of entropy as a measure of dividedness and dispersion more broadly in his development of his "evenness of spread" entropy concept, and provides the basis of the development of a more formal model of organizational citizenship entropy.…”
Section: The Development Of a Model Of Organizational Citizenship Entmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the heuristic is unable to articulate formally the distribution of personal and organizational citizenship behavior that leads to ECB. It is maintained in the current paper that Theil's [8] "evenness of spread" concept can provide the basis for a sounder, more formal and detailed development of the original Coldwell and Callaghan [23] model. Theil [8] uses Shannon's notion of entropy as a measure of dividedness and dispersion more broadly in his development of his "evenness of spread" entropy concept, and provides the basis of the development of a more formal model of organizational citizenship entropy.…”
Section: The Development Of a Model Of Organizational Citizenship Entmentioning
confidence: 99%
“…It follows that the more Entropic Citizenship Behavior (ECB) becomes a group level phenomenon in departments constituting an organization, the greater threat it is to the achievement of its goals and its ultimate sustainability. Very briefly, Coldwell and Callaghan [23] in their study of organizational citizenship behavior, found examples from military history and business of the negative effects of extreme forms of personal or organizational citizenship behavior on organizational performance. Examples of fraternization with the enemy in the First World War where British and German frontline soldiers on both sides became involved in initiating non-lethal war activities that acted out belligerence without harmful intent Axelrod [24] demonstrated the effects of extreme personal oriented citizenship behavior where care for survival overrode the Militia's goal on both sides to wage aggressive and lethal warfare to destroy the enemy.…”
Section: The Concept Of Organizational Citizenship Entropymentioning
confidence: 99%
See 2 more Smart Citations
“…Organ (1988) and other researchers regard the extra-role behaviour that contributes to organisational effectiveness by improving individual and work group performance and organisational morale to be organisational citizenship or 'good soldier' behaviour (Organ 1988;Smith, Organ and Near 1983). The term 'good soldier' was incorporated into the concept of OCB and is regarded as transferable to organisations designed for specific purposes, such as political organisations (Graham 1991), the military from which the concept is derived, and business organisations (Borman, Motowidlo, Rose, and Hanser 1983;Coldwell and Callaghan 2014 Borman's (2004) model, consisting essentially of the two main dimensions of personal and organisational support behaviour (including conscientious initiative as it pertains to both aspects), provides the basis for the development of the quantitative and qualitative instruments used in the study. Conscientious initiative through its duality of relevance to both personal and organisational aspects of OCB can be regarded as its core underlying dimension.…”
Section: Organisational Citizenship Behaviourmentioning
confidence: 99%